WESTERN EDUCATIONAL PHILOSOPHIES IN THE PERSPEKTIF OF ISLAMIC EDUCATION: A PHILOSOPHICAL FILTERING FRAMEWORK BASED ON TARBIYAH, TA’LIM, DAN TAZKIYAH - Darnanengsih Darnanengsih; Masriwaty; Afifuddin; Marjuni; Rusyaid Rusyaid (IAIN Bone, 2026)
This article analyzes the major schools of educational philosophy idealism, realism, materialism, pragmatism, and existentialism within the framework of Islamic education and the contemporary Indonesian educational context. Using a qualitative library research method, this study examines classical and contemporary literature to explore the ontological, epistemological, and axiological foundations of each philosophical school. The findings indicate that these schools emerged from specific historical and social contexts and offer distinct yet complementary perspectives on educational aims and practices. The study further reveals that the Islamic educational concepts of tarbiyah, ta’lim, and tazkiyah provide an integrative framework capable of synthesizing diverse philosophical traditions while maintaining the normative orientation of Islamic education. In the Indonesian context, particularly under the implementation of the Merdeka Curriculum, these philosophical schools remain relevant when applied flexibly and contextually to support character education, competency development, and learner autonomy. This study concludes that an integrative and complementary philosophical approach is essential for developing holistic and responsive educational practices in contemporary Islamic education